2012
DOI: 10.3892/mmr.2012.813
|View full text |Cite
|
Sign up to set email alerts
|

Calcium oxalate monohydrate crystals stimulate monocyte chemoattractant protein-1 and transforming growth factor β1 expression in human renal epithelial cells

Abstract: Abstract. Crystal-cell interactions play a key role in the formation of kidney stones. Few studies have referred to the role of monocyte chemoattractant protein-1 (MCP-1) and transforming growth factor β1 (TGFβ1) in kidney stone formation. Recently, a genome-wide analysis of genes related to kidney stone formation and eliminiation in mice indicated that MCP-1 and TGFβ1 are involved in nephrolithiasis. In this study, in order to verify whether MCP-1 and TGFβ1 are involved in the process of crystal-cell interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The G allele of CCL2 rs1024611, which is known to be a risk allele for inflammatory infective and non-infective diseases 28 29 , could simultaneously participate in progressing chronic kidney disease in nephrolithiasis patients as indicated by the interaction of CCL2 rs1024611 with CASR rs7652589 in the studied HD subjects. Moreover, CCL2 expression was found to be induced by calcium oxalate monohydrate in renal epithelial cells 30 . Suppression of CCL2 mRNA expression and downregulation of the expression of CCL2 -related proteins including transforming growth factor beta-1 by resveratrol in oxalate-treated human renal epithelial cells significantly reduced the number of urine calcium oxalate crystals 31 .…”
Section: Discussionmentioning
confidence: 97%
“…The G allele of CCL2 rs1024611, which is known to be a risk allele for inflammatory infective and non-infective diseases 28 29 , could simultaneously participate in progressing chronic kidney disease in nephrolithiasis patients as indicated by the interaction of CCL2 rs1024611 with CASR rs7652589 in the studied HD subjects. Moreover, CCL2 expression was found to be induced by calcium oxalate monohydrate in renal epithelial cells 30 . Suppression of CCL2 mRNA expression and downregulation of the expression of CCL2 -related proteins including transforming growth factor beta-1 by resveratrol in oxalate-treated human renal epithelial cells significantly reduced the number of urine calcium oxalate crystals 31 .…”
Section: Discussionmentioning
confidence: 97%
“…Consumption of meals rich in oxalate augments urinary oxalate excretion potentially leading to new kidney stone formation, growth of existing stones, and in some instances renal damage (12). Experimental studies have shown renal epithelial cells exposed to oxalate have reduced glutathione levels (18), impaired DNA synthesis (19,20), and increased reactive oxygen species (ROS) generation (18,(20)(21)(22)(23), mitochondrial permeability transitionmediated cell death (24), and monocyte chemoattractant protein (MCP-1) secretion (25,26). MCP-1 is a cytokine that recruits monocytes and macrophages to tissues to remove dead cells, pathogens, and crystals (27).…”
Section: Introductionmentioning
confidence: 99%
“…CaOx crystals form when the urine becomes supersaturated with calcium and oxalate. Several studies have reported that crystals and oxalate stimulate inflammatory responses, including monocyte chemoattractant protein-1 (MCP-1) release in renal epithelial cells [8] , [9] , [10] , [11] , [12] . MCP-1 plays an important role in monocyte/macrophage recruitment and activation, and has been shown to be elevated in the urine and renal tissue of patients with kidney stones [13] , [14] .…”
Section: Introductionmentioning
confidence: 99%